Biallelic truncating variants in children with titinopathy represent a recognizable condition with distinctive muscular and cardiac characteristics: a report on five patients - Baban, Anwar; Cicenia, Marianna; Magliozzi, Monia; Parlapiano, Giovanni; Cirillo, Marco; Pascolini, Giulia; Fattori, Fabiana; Gnazzo, Maria; Bruno, Pasqualina; De Luca, Lorenzo; Di Chiara, Luca; Francalanci, Paola; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Monoallelic and biallelic TTN truncating variants (TTNtv) may be responsible for a wide spectrum of musculoskeletal and cardiac disorders with different age at onset. Although the prevalence of heterozygous TTNtv is relatively high in the general population, cardiac phenotyping (mainly cardiomyopathies, CMPs) in biallelic titinopathy has rarely been described in children. Methods We reviewed the medical records of pediatric patients with biallelic TTNtv and cardiac involvement. Clinical exome sequencing excluded pathogenic/likely pathogenic variants in major CMP genes. Results Five pediatric patients (four male) with biallelic TTNtv were included. Major arthrogryposis multiplex was observed in four patients; no patient showed intellectual disability. At a cardiac level, congenital heart defects (atrial and ventricular septal defects, n = 3) and left ventricular non-compaction (n = 1) were reported. All patients had dilated cardiomyopathy (DCM) diagnosed at birth in one patient and at the age of 10, 13, 14, and 17 years in the other four patients. Heart rhythm monitoring showed tachyarrhythmias (premature ventricular contractions, n = 2; non-sustained ventricular tachycardia, n = 2) and nocturnal first-degree atrio-ventricular block (n = 2). Cardiac magnetic resonance (CMR) imaging was performed in all patients and revealed a peculiar late gadolinium enhancement distribution in three patients. HyperCKemia was present in two patients and end-stage heart failure in four. End-organ damage requiring heart transplantation (HT) was indicated in two patients, who were operated on successfully. Conclusion Biallelic TTNtv should be considered when evaluating children with severe and early-onset DCM, particularly if skeletal and muscular abnormalities are present, e.g., arthrogryposis multiplex and congenital progressive myopathy. End-stage heart failure is common and may require HT.